2017
DOI: 10.1051/0004-6361/201630094
|View full text |Cite
|
Sign up to set email alerts
|

Importance of fingering convection for accreting white dwarfs in the framework of full evolutionary calculations: the case of the hydrogen-rich white dwarfs GD 133 and G 29-38

Abstract: Context. A large fraction of white dwarf stars show photospheric chemical composition polluted by heavy elements accreted from a debris disk. Such debris disks result from the tidal disruption of rocky planetesimals which had survived to whole stellar evolution from the main sequence to the final white dwarf stage. Determining the accretion rate of this material is an important step towards estimating the mass of the planetesimals and towards understanding the ultimate fate of the planetary systems. Aims. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
2
42
0
Order By: Relevance
“…Figure 4 also compares against MESA calculations assuming only diffusion governs the equilibrium state, where we use Equation 4 to inferṀ acc , and assume bulk earth abundances for the accreted material. For objects with T eff > 10, 000 K, the inferred accretion rate can increase by several orders of magnitude when accounting for thermohaline mixing, confirming the earlier work of Deal et al (2013) and Wachlin et al (2017).…”
Section: Accretion Rates and Compositionssupporting
confidence: 81%
See 2 more Smart Citations
“…Figure 4 also compares against MESA calculations assuming only diffusion governs the equilibrium state, where we use Equation 4 to inferṀ acc , and assume bulk earth abundances for the accreted material. For objects with T eff > 10, 000 K, the inferred accretion rate can increase by several orders of magnitude when accounting for thermohaline mixing, confirming the earlier work of Deal et al (2013) and Wachlin et al (2017).…”
Section: Accretion Rates and Compositionssupporting
confidence: 81%
“…Hence, we infer an accretion rate that is 40% larger than the value Xu et al (2014) report, but we find excellent agreement with their relative diffusion timescales and composition of the accreted material. Deal et al (2013) and Wachlin et al (2017) have noted that thermohaline mixing may significantly alter the accretion rates inferred from observed abundances in polluted WDs. Koester (2015) argued against the efficacy of this instability for a few cases.…”
Section: Gravitational Sedimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Corresponding author: Evan B. Bauer ebauer@physics.ucsb.edu While many have relied on elemental sedimentation timescales to make inferences about polluted WD accretion, recent work has revealed that thermohaline instability is active and substantially modifies the inferred accretion rateṀ acc (Deal et al 2013;Wachlin et al 2017). Our work in Bauer & Bildsten (2018, Paper I) greatly expanded the range of T eff explored for polluted WD models accounting for thermohaline mixing.…”
Section: Introductionmentioning
confidence: 90%
“…The presence of metals in the envelope can themselves lead to sharp gradients in density, triggering instabilities such as the thermohaline (fingering) instability. This can lead to an under-prediction of accretion rates by orders of magnitude (Deal et al 2013;Bauer & Bildsten 2018;Bauer & Bildsten 2019;Wachlin et al 2017), although its application to white dwarf convection zones has been questioned (Koester 2015). It is, however, clear from the above papers that the thermohaline instability is not important for the cool, helium-rich white dwarfs considered in this work.…”
Section: O R I Gmentioning
confidence: 99%